2003
DOI: 10.1021/la020811b
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Carbon−Carbon Bond Formation in Water-in-Oil Highly Concentrated Emulsions (Gel Emulsions)

Abstract: Water-in-oil (W/O) highly concentrated emulsions (gel emulsions) of water/C14E4/aliphatic hydrocarbon systems were investigated as reaction media for the aldolic condensation of dihydroxyacetone phosphate (DHAP) with acceptor aldehydes such as phenylacetaldehyde (1) and benzyloxyacetaldehyde (2), catalyzed by D-fructose-1,6-bisphosphate aldolase from rabbit muscle (RAMA). Prior to any enzymatic reaction, both the formation and stability of the W/O gel emulsions in the presence of reactants were assessed. It wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 58 publications
0
21
0
Order By: Relevance
“…Furthermore, on increasing the reactant concentration up to [DHAP] = 100 mm and [N-Cbz-aminoaldehyde] = 170 mm (see Supporting Information) conversions for RhuA-and FucA-catalyzed reactions were generally higher in emulsion than those in 1:4 DMF/H 2 O, probably because of the better solubilization properties of the former reaction medium. [37] Investigations of temperature effects: Temperature effects were also investigated for RhuA aldolization of aldehydes (R)-2 a, (R)-2 b (vide infra), (R)-2 c, (R)-2 f, and (S)-2 f. To this end, the selected reactions were conducted at 4 8C, because it has been reported that at this temperature the conversion achieved on FucA-catalyzed aldol addition of DHAP to (R)-N-Cbz-alaninal was significantly improved. [38] Interestingly, there were temperature effects on the stereoselectivity of the enzymatic reactions (vide infra), but no improvement on aldol conversions was observed for any of the selected examples, indicating that this phenomenon is not of general applicability.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, on increasing the reactant concentration up to [DHAP] = 100 mm and [N-Cbz-aminoaldehyde] = 170 mm (see Supporting Information) conversions for RhuA-and FucA-catalyzed reactions were generally higher in emulsion than those in 1:4 DMF/H 2 O, probably because of the better solubilization properties of the former reaction medium. [37] Investigations of temperature effects: Temperature effects were also investigated for RhuA aldolization of aldehydes (R)-2 a, (R)-2 b (vide infra), (R)-2 c, (R)-2 f, and (S)-2 f. To this end, the selected reactions were conducted at 4 8C, because it has been reported that at this temperature the conversion achieved on FucA-catalyzed aldol addition of DHAP to (R)-N-Cbz-alaninal was significantly improved. [38] Interestingly, there were temperature effects on the stereoselectivity of the enzymatic reactions (vide infra), but no improvement on aldol conversions was observed for any of the selected examples, indicating that this phenomenon is not of general applicability.…”
Section: Resultsmentioning
confidence: 99%
“…Final yields and stereoselectivity are depending on the aldehyde and enzyme employed. The influence of reaction medium on the synthesis performance has also been studied (Espelt et al, 2003b). Nevertheless, the practical application of aldolase catalyzed processes in chiral synthesis requires appropriate reactor design based on a deep knowledge of reactions behavior, and improvement of the synthesis yields which are often relatively low.…”
Section: Introductionmentioning
confidence: 99%
“…[15] Emulsions and DMF/buffer (1:4 v/v) were the reaction systems of choice at both 25 8C and 4 8C. The literature precedent from enzymatic DHAP aldol addition studies demonstrated that the conversions may be influenced by the reaction media, [16] and improved at 4 8C. [17] The enzymatic reactions were incubated until constant conversion values were monitored.…”
mentioning
confidence: 99%